TanDEM-X going for the DEM: Acquisition, Performance, and further Activities - Tridon, Daniela Borla; Bachmann, Markus; Böer, Johannes; Bräutigam, Benjamin; Gonzalez, Carolina; Kraus, Thomas; Krieger, Gerhard; Martone, Michele; Polimeni, Maria Donata; Schulze, Daniel; Wecklich, Christopher; Zink, Manfred (Asia-Pacific Conference on Synthetic Aperture Radar (APSAR), 2015)
TanDEM-X is an innovative spaceborne X-band SAR mission designed to derive a digital elevation model (DEM) of the Earth′s land surface with an unprecedented relative vertical accuracy of 2m at a 12m posting. The global DEM is derived from interferometric SAR acquisitions performed by two radar satellites flying in close orbit formation, with adjustable baselines in cross- and in along-track directions. This paper provides an overview of the present mission status in terms of acquisition strategy and a quality summary of the currently available parts of the TanDEM-X global DEM in terms of absolute and relative height accuracy
DLR Import::2019-04-03
Keywords: absolute/relative height accuracy; bistatic formation; Digital Elevation Model (DEM); SAR Interferometry; TanDEM-X